Roman Gods and Private Property: The Invention of State Religion in Cicero's Speech On His House - Rüpke, Jörg (Religion in the Roman empire, 2019)
The transformation of the home of the exiled Marcus Tullius Cicero into a sacred space by his opponent, the pontifex Clodius, sheds light on religious appropriations and demarcations against religion in an urban context. The source situation is peculiar, since it is the person at the heart of the dispute who describes his perception of the problem in the two relevant preserved speeches. However, the scope of the speech (De domo sua) given before the responsible religious specialists, the pontiffs, allows for a detailed analysis of the issues. This study takes seriously the fact that the author pursues a clear goal, the restitution of his property. My thesis is that, in order to achieve this goal, Cicero presents and systematises different normative positions and practices as historically verifiable or even already asserted. On this basis he develops a restrictive concept of those religious practices that can claim a generally binding force, that is, that can bind both Roman legal and political institutions as well as individuals in the city of Rome. To make my claim plausible, I follow Cicero's argumentation in its interplay of examples and generalisations. The investigation demonstrates the extent to which this text, which has generally been accepted as an impartial description of the fundamentals of 'Roman religion' as a religious 'system' that is very closely bound to politically legitimised actors, in fact represents only one position in a sharp confrontation (albeit the victorious one in this particular conflict).